Disruption of reproductive and thyroid endocrine systems in zebrafish following early life and whole life cycle exposure to low-dose norgestrel - Shuyan Mai; Weicai Hu; Yan-Qiu Liang; Zhongdian Dong; Chang-Gui Pan; Zhiyun Liu; Runting Ouyang; Yangjie Zeng; Zhong Lin; Liping Hou (Ecotoxicology and Environmental Safety)
Norgestrel (NGT), a synthetic progestin, is frequently detected in aquatic environments and known to disrupt fish endocrine systems. In this study, zebrafish embryos were exposed to low NGT concentrations (9 and 66 ng/L) for 90 days post-fertilization (dpf), covering embryonic-juvenile (0–30 dpf) and juvenile-adult stages (31–90 dpf, with/without continuous exposure to NGT). Body length, weight, hormone levels of whole fish, and gene expression related to sex differentiation, hypothalamic-pituitary-gonadal (HPG) and hypothalamic-pituitary-thyroid (HPT) axes were analyzed. The results showed that early life NGT exposure impaired juvenile growth, with effects persisting into adulthood and worsening under continuous exposure. NGT severely disrupted reproductive development: during early life stages, it suppressed follicle-stimulating hormone (FSH) and luteinizing hormone (LH) levels while downregulating the female differentiation gene (figa) and steroidogenic genes, skewing the adult sex ratio toward males. In adulthood, NGT further disrupted steroidogenic and receptor genes expression. Whole life cycle exposure exacerbated male bias, impaired HPG axis-related genes expression, and hindered testicular development. In contrast, the thyroid system exhibited lower sensitivity to NGT. Early life exposure reduced thyroid-stimulating hormone (TSH) levels, suggesting hypothyroidism, while upregulating HPT axis-related genes (dio2 and tpo). By adulthood, only trh transcription remained elevated. Whole life cycle exposure suppressed tshb and thrb expression in the HPT axis. In summary, NGT exposure caused significant and lasting disruptions to zebrafish growth and endocrine function. This study highlighted the potential irreversible harm of synthetic progestins in aquatic ecosystems and underscores the need for stricter regulation of these contaminants in water systems.